1996
DOI: 10.1002/(sici)1097-0223(199606)16:6<564::aid-pd903>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Duodenal Atresia and Possible Sonographic Pitfalls

Abstract: The sonographic diagnosis of duodenal atresia and associated anomalies was made in a fetus at 15 weeks' gestation. A transient double‐bubble sign was observed in three other normal fetuses. Sonographers are cautioned that normal intestinal peristalsis may cause a false image of duodenal atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…This study found a similar PPV for both duodenal and jejunoileal obstructions for all cases suspected in the second and third trimesters within the cohort (90.4% and 88.2% respectively). This was not previously reported as PPV is typically thought to be much higher in duodenal obstructions due to the highly suggestive ultrasound sign of the double bubble 27,28 . However, it is known that the contraction of the stomach can create a false‐positive finding of a double bubble, mimicking a duodenal obstruction in healthy fetuses 29 .…”
Section: Discussionmentioning
confidence: 85%
“…This study found a similar PPV for both duodenal and jejunoileal obstructions for all cases suspected in the second and third trimesters within the cohort (90.4% and 88.2% respectively). This was not previously reported as PPV is typically thought to be much higher in duodenal obstructions due to the highly suggestive ultrasound sign of the double bubble 27,28 . However, it is known that the contraction of the stomach can create a false‐positive finding of a double bubble, mimicking a duodenal obstruction in healthy fetuses 29 .…”
Section: Discussionmentioning
confidence: 85%
“…The double bubble sign of proximal duodenal obstruction can be detected from the second trimester onward. 5,6 There is a high prevalence of associated structural anomalies (50%) and trisomy 21 (30%). 7 The differential diagnosis includes other extrinsic or intrinsic causes for duodenal obstruction, for example, annular pancreas, intestinal malrotation with the Ladd bands, gastrointestinal duplication cysts, duodenal web, preduodenal portal vein, and choledochal cyst.…”
Section: Discussionmentioning
confidence: 99%
“…The double bubble sign of proximal duodenal obstruction can be detected from the second trimester onward 5,6 . There is a high prevalence of associated structural anomalies (50%) and trisomy 21 (30%) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The amniotic fluid-filled “double bubble” may represent an intrinsic or extrinsic obstruction [3]. To confirm duodenal obstruction is important to visualize the dilated duodenum for several minutes as it is possible that intestinal peristalsis in a fetus may show transient dilatation suggesting duodenal obstruction [4]. It is also important to demonstrate the continuity between the gastric and duodenal bubbles to exclude other causes.…”
Section: Introductionmentioning
confidence: 99%